Pain management in chronic kidney disease patients - Jirirasin, Sitta; Kantachuvesiri, Surasak (Journal of the Nephrology Society of Thailand, 2022)
Pain is one of common complaints in patients with chronic kidney disease, which if not properly managed, can lead to other adverse effects such as sleep disturbance, limitations in work and daily life, poor quality of life, and missed treatment session in dialysis-patients. Key factors in pain assessment include pain severity, chronicity of pain, nature of pain, and treatment goals. To achieve better treatment results, all of these factors should be evaluated and the appropriate medications can then be prescribed. Currently the main pain medications are paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs) and opioids. All of which have altered pharmacokinetics and side effects are more common in patients with impaired renal function. Selection of drugs is recommended to consider all factors mentioned above. Paracetamol should be prescribed in people with mild pain. If symptoms do not improve or patients with moderate to severe pain then consider using non-steroidal anti-inflammatory drugs or opioids. This article describes how to evaluate pain and select appropriate drugs for pain control in patients with impaired kidney function.